Analisis Pertanggungjawaban Pidana Korporasi Pada Pembakaran Lahan Berdasarkan Teori Strict Liability - Cristian Andros; Gunawan Djajaputera (LPPM Universitas Ekasakti Padang, 2024)
Forest and land fires have widespread and serious impacts. Environmentally, these fires cause ecosystem damage, loss of biodiversity, and contribute to climate change through high carbon emissions. In terms of health, the smoke produced from forest fires can cause respiratory problems and other diseases in local communities. Law no. 32 of 2009 concerning Environmental Protection and Management (UUPPLH) regulates the principle of strict liability which is limited to cases involving the use and management of Hazardous and Toxic Substances (B3). Article 88 of the UUPPLH states that every person whose actions pose a serious threat to the environment as a result of the use or management of B3 waste is absolutely responsible for the losses incurred without the need for proof of fault. The explanation of Article 88 also emphasizes that this principle is applied in the context of civil lawsuits, not criminal ones. In the Meulaboh District Court Decision Number 54/Pid.Sus/2014/PN.MBO, PT. Surya Panen Subur (SPS) was charged with Article 108 Jo Article 69 paragraph (1) letter h Jo Article 116 paragraph (1) letter a UUPPLH Jo. Article 64 paragraph (1) of the Criminal Code. The judge decided that PT. SPS is criminally responsible based on the principle of strict liability due to the burning of land managed by the company. However, this approach shows a lack of rigor and inconsistency in legal considerations.